The Cultural Shock Phenomenon of Chinese People in Indonesia: A Case Study of Cross-cultural Communication - Liu Dandan (IAHN-TP Palangka Raya, 2024)
Cultural exchanges between China and Indonesia have also begun to increase year by year. More and more Chinese companies and people are coming to Indonesia to invest and work. Due to differences in values, social norms, cultural norms, and customs between China and Indonesia, Chinese newcomers to Indonesia will feel a cultural shock. This research, hence, aims to present the psychological pain points that exhibit in the cross-cultural communication among Indonesian Chinese people through case studies by analyzing the language and cultural differences between China and Indonesia. The results have revealed a number of differences in language and culture between China and Indonesia. Finally, it is expected that these findings help both Chinese and Indonesian people to avoid cultural conflicts, better engage in cultural and educational exchange activities, and increase the probability of success in cross-cultural communication.